Analysis of the Ease of Micro IB Financing at PT BSI KCP Kampung Tax in the Covid-19 Pandemic Period - Intan Dinda Sutantri; Sugianto Sugianto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The COVID-19 pandemic has had an impact on the Indonesian economy. The decline in economic performance is not only experienced by large multinational and national industries, but also experienced by MSME actors. This research aims to identify the usability of social funds in Islamic banks for MSMEs due to the Covid-19 pandemic. The approach used in this research is qualitative. The author uses secondary data from various literatures such as books, and homepages to access the latest information and data related to the policy of saving MSMEs due to the COVID-19 pandemic. The author said that Islamic banking, especially at the Sharia Bank KCP Kampung Tax serves to protect MSMEs during the Covid-19 pandemic, by helping the distribution of government programs, namely KUR (People's Business Credit) providing concessions to entrepreneurs affected by the Covid-19 pandemic and facilitating the financing process. for entrepreneurs as has been inaugurated by the government through PJOK Regulation No. 11 of 2020.